أثر الإجراءات القطرية في مقومات التعايش على التعايش السلمي في دولة قطر: The Impact Of Qatari Procedures In The Elements Of Coexistence On Peaceful Coexistence In The State Of Qatar - Kawthar Abdalla Bayouomi; Hind Mohammad Ahmed Al-Hammadi (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
The State of Qatar has a great record in the field of coexistence and peace, which is part of the state's internal and external policy amidst a world full of conflicts. The State of Qatar has the highest percentage of immigrants in the world, so it has been keen to manage this population diversity efficiently to achieve peaceful coexistence as a lofty civilized goal that humanity strives for, in accordance with its religious authority and civil laws, procedures that are in line with international treaties and agreements that it has ratified. This topic was chosen based on the fact that Qatar ranked first regionally and had advanced degrees globally in the Global Peace Index (IEP), and it seek to answer the main study question which is: To what extent are the population groups of expatriate workers satisfied with the Qatari measures in the economic, social, cultural and legal aspects to support and promote the peaceful coexistence in the State of Qatar in light of the Qatari immigration objectives for the Alliance of Civilizations? The empirical study followed the descriptive analytical approach, and the questionnaire and interview tool to collect information from a sample of (2401 respondents) to assess the extent of satisfaction of population groups of expatriate workers with the Qatari measures in the economic, social, cultural and legal aspects to support and promote the peaceful coexistence in the State of Qatar in light of the objectives of the Qatari immigration for the Alliance of Civilizations as a main objective of the study, during the period from 2015-2022. The study came out with several results: there is a high satisfaction rate of (83.7%), and an arithmetic average of (3.04) about the measures taken by Qatar with regard to managing population diversity through the elements of peaceful coexistence. The study recommended investing the Qatari model in managing population diversity to spread the values of tolerance and peaceful coexistence globally especially towards minorities who suffer injustice and persecution in some countries of the world, increasing interest in the Arabic language by Qatar by obliging expatriates to learn its basics to achieve more harmony and integration, and to highlight the value of equality in dealing with others from a religious and international standpoint for the advancement of society. Keywords: Qatar, Coexistence, Immigration, Peace, Alliance Of Civilizations